Strategi Penguatan Profil Pelajar Pancasila Melalui Kegiatan Gorelasi Sebagai Budaya Sekolah di SMP Negeri 6 Medan (Jurnal Sosial Humaniora dan Pendidikan, 2025)
GORELASI (mutual cooperation, creativity, religion and literacy) is an activity that has become a school culture at SMP Negeri 6 and as a strategy to strengthen the profile of Pancasila students to create students with Pancasila character amidst many student problems regarding moral degradation. The purpose of this study is to determine the implementation of GORELASI activities as a school culture that is a strategy in realizing the Pancasila Student Profile at SMP Negeri 6 Medan, to find out the supporting factors and inhibiting factors in the implementation of GORELASI activities, to find out whether GORELASI activities as a strategy to strengthen the profile of Pancasila students can improve the character of students who are Faithful and have noble morals, Independent, Mutual Cooperation, Global Diversity, Critical and Creative Reasoning. The type of research used is descriptive research with qualitative research methods. Data collection techniques using interviews, observations, and document studies. Data analysis goes through three stages, namely data reduction (Data Reduction), data presentation (Data display) and drawing conclusions (Data Verification). The results of the research obtained are that the GORELASI Activity at SMP Negeri 6 Medan was implemented very well through four (4) strategies, namely Strengthening the Pancasila Student Profile through Tuesday Creation, Wednesday Literacy, Thursday mutual cooperation and Friday Religion which were carried out as weekly routine activities. The GORELASI activity was implemented as a strategy for building student character because it provided space and concrete experiences for students to learn about values (moral knowing), feel and internalize values (moral feeling), live and practice values in life (moral action) so that they could form and develop as well as strengthen and improve the character of Pancasila Students who are Faithful, Devout to God Almighty and have Noble Morals, Independent, Mutual Cooperation, Global Diversity, Critical and Creative Reasoning in accordance with Permendikbud Number 22 of 2020 concerning the Strategic Plan of the Ministry of Education, Culture, Research and Technology for 2020-2024.